2017
DOI: 10.1002/fam.2448
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing egress drills: Preparation and assessment of evacuee performance

Abstract: Summary This article explores how egress drills—specifically those related to fire incidents—are currently used, their impact on safety levels, and the insights gained from them. It is suggested that neither the merits of egress drills are well understood, nor the impact on egress performance well characterized. In addition, the manner in which they are conducted varies both between and within regulatory jurisdictions. By investigating their strengths and limitations, this article suggests opportunities for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(68 citation statements)
references
References 46 publications
0
68
0
Order By: Relevance
“…However, these traditional approaches may not effectively transmit knowledge (Gwynne, Boyce, Kuligowski, Nilsson, P. Robbins, & Lovreglio, 2016). One reason is that after an evacuation drill, building occupants are generally not provided with individual feedback assessing their evacuation behavior (Gwynne, Kuligowski, Boyce, Nilsson, Robbins, Lovreglio et al, 2017). Another reason is that building occupants can be not emotionally engaged in the learning process that may lead to a reduced effect on attitude and limited change in behavior (Chittaro, Buttussi, & Zangrando, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these traditional approaches may not effectively transmit knowledge (Gwynne, Boyce, Kuligowski, Nilsson, P. Robbins, & Lovreglio, 2016). One reason is that after an evacuation drill, building occupants are generally not provided with individual feedback assessing their evacuation behavior (Gwynne, Kuligowski, Boyce, Nilsson, Robbins, Lovreglio et al, 2017). Another reason is that building occupants can be not emotionally engaged in the learning process that may lead to a reduced effect on attitude and limited change in behavior (Chittaro, Buttussi, & Zangrando, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Yang et al (2011) pointed out that real-life evacuation behavior is different from experiments such as evacuation drills, which means that current evacuation models still have limitations when they are the basis of evacuation training and research. Evacuation drills also have other limitations such as being costly in time and resources by interrupting building occupants' routines, and being not able to present hazards (Gwynne et al, 2016;Gwynne et al, 2017;Silva, Almeida, Rossetti, & Leca Coelho, 2013). Therefore, there is a need to investigate innovative and more effective approaches to overcome the limitations mentioned above (Kobes, Helsloot, de Vries, & Post, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Laboratory and field experiments are essential to understand pedestrian behavior, but they need participants and bind a lot of scientific and non-scientific human resources. Here simulations can help out [29,28]. Also, they are generally more time-efficient.…”
Section: Introductionmentioning
confidence: 99%
“…A known example is the case of the 2001 World Trade Center terrorist attacks in which instructions to remain in the stricken building were given to employees working in the WTC during the attack [19]. In contrast, survivors' accounts demonstrated that in some instances an independent evacuee's decision made in conflict with the order received, can save lives.On the one hand, authorities should not ignore bomb threats given the risk of losing human lives.On the other hand, multiple unnecessary evacuations (drills, false threats) may lead to a decrease in the authority credibility and people's underestimation of threats [20,21]. This is called the cry wolf effect in reference to Aesop's fable The Boy who Cried Wolf in which instruction compliance is decreased by a series of false alarms [22].…”
mentioning
confidence: 99%
“…On the other hand, multiple unnecessary evacuations (drills, false threats) may lead to a decrease in the authority credibility and people's underestimation of threats [20,21]. This is called the cry wolf effect in reference to Aesop's fable The Boy who Cried Wolf in which instruction compliance is decreased by a series of false alarms [22].…”
mentioning
confidence: 99%